2017
DOI: 10.1103/physrevd.96.094010
|View full text |Cite
|
Sign up to set email alerts
|

New insights into hadron production mechanism from pT spectra in pp collisions at s=7

Abstract: We show that the experimental data of mid-rapidity p T spectra for proton, Λ, Ξ , Ω − , K(892) * 0 and Ξ(1530) * 0 in minimum-bias pp collisions at √ s = 7 TeV can be systemically explained by the quark combination mechanism of hadronization. The averaged transverse momentum p T and spectra ratios such as Ξ/Λ and Ω/φ calculated from quark combination reproduce the data much better than those from traditional string and/or cluster fragmentation. The available data of hadronic p T spectra released by ALICE colla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 63 publications
(181 reference statements)
2
37
0
Order By: Relevance
“…The p T distributions of quarks at hadronization are inputs of the model. We have obtained the p T spectra of light-flavor constituent quarks in the previous work [21]. The averaged quark numbers in the rapidity interval |y| < 0.5 are 2.5 for the u quark and 0.8 for the s quark, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The p T distributions of quarks at hadronization are inputs of the model. We have obtained the p T spectra of light-flavor constituent quarks in the previous work [21]. The averaged quark numbers in the rapidity interval |y| < 0.5 are 2.5 for the u quark and 0.8 for the s quark, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We emphasize the following aspects to address the physical importance of our results: (1) The property, i.e., the p T distributions, of light-flavor constituent quarks and antiquarks at hadronization is obtained from the data of p T spectra of light-flavor hadrons in work [21] where it is found that equal-velocity combination of light-flavor quarks can reasonably describe the data of light-flavor hadrons in the low p T range. The existence of the underlying source of light-flavor quarks is a new property of small parton system, maybe related to the creation of the deconfined parton system in pp collisions at LHC energies.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations